Contract and domination - Pateman, Carole; Mills, Charles W. (Polity, 2007)
« Contract and Domination offers a bold challenge to contemporary contract theory, arguing that it should either be fundamentally rethought or abandoned altogether. Since the publication of John Rawls's A Theory of Justice, contract theory has once again become central to the Western political tradition. But gender justice is neglected and racial justice almost completely ignored. Carole Pateman's and Charles Mills's earlier books, The Sexual Contract (1988) and The Racial Contract (1997), offered devastating critiques of gender and racial domination and the contemporary contract tradition's silence on them. Both books have become classics of revisionist radical democratic political theory. Now Pateman and Mills are collaborating for the first time in an interdisciplinary volume, drawing on their insights from political science and philosophy. They are building on but going beyond their earlier work to bring the sexual and racial contracts together. In Contract and Domination, Pateman and Mills discuss their differences about contract theory and whether it has a useful future; excavate the (white) settler contract that created new civil societies in North America and Australia; argue via a "non-ideal" contract for reparations to black Americans; confront the evasions of contemporary contract theorists; explore the intersections of gender and race and the global sexual-racial contract; and reply to their critics. »–Page 4 de la couverture.
Section: ix, 306 pages ; 24 cm.
Keywords: approches et analyses; capitalisme; com5170; contrat social; cours; discipline; histoire et politique; intersectionnalité; patriarcat; philosophie; philosophie politique; pol4212; premier cycle; racisme; rapports de domination; science politique; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques

L'ONU, alliée des femmes ? Une analyse féministe du système des organisations internationales - Falquet, Jules (Multitudes, 2003)
Cet article analyse la stratégie du système onusien pour neutraliser les mouvements sociaux contestataires en les faisant « participer » à son projet de « bonne gouvernance » mondiale, à travers l’exemple du mouvement féministe latino-américain et des Caraïbes. En étudiant les « politiques de population » des institutions internationales et la question du micro-crédit pour les femmes, on voit comment l’ONU parvient à se présenter comme « alliée » des femmes et à embrigader dans son entreprise une partie du mouvement féministe, alors qu’elle applique des politiques désastreuses pour les femmes, en particulier pour les femmes pauvres du Sud.
Keywords: amérique latine; amériques; approches et analyses; capitalisme; caraïbes; cours; discipline; histoire et politique; inégalités; oppressions institutionelles; philosophie; pol4022; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques